Omeprazole, a Gastric Proton Pump Inhibitor, Inhibits Melanogenesis by Blocking ATP7A Trafficking - Matsui, Mary S.; Petris, Michael J.; Niki, Yoko; Karaman-Jurukovska, Nevena; Muizzuddin, Neelam; Ichihashi, Masamitsu; Yarosh, Daniel B. (Journal of investigative dermatology, 2015)
Omeprazole is a proton pump inhibitor used in the treatment of peptic ulcer disease and gastrosophageal reflux disease and acts by irreversibly blocking ATP4A, a P-type H+/K+ ATPase in gastric parietal cells. We found that omeprazole and its closely related congeners inhibited melanogenesis at micromolar concentrations in B16 mouse melanoma cells, normal human epidermal melanocytes, and in a reconstructed human skin model. Omeprazole topically applied to the skin of UV-irradiated human subjects significantly reduced pigment levels after 3 weeks compared with untreated controls. Omeprazole had no significant inhibitory effect on the activities of purified human tyrosinase or on the mRNA levels of tyrosinase, dopachrome tautomerase, Pmel17, or MITF mRNA levels. Although melanocytes do not express ATP4A, they do express ATP7A, a copper transporting P-type ATPase in the trans-Golgi network that is required for copper acquisition by tyrosinase. ATP7A relocalization from the trans-Golgi network to the plasma membrane in response to elevated copper concentrations in melanocytes was inhibited by omeprazole. Omeprazole treatment increased the proportion of EndoH sensitive tyrosinase, indicating that tyrosinase maturation was impaired. In addition, omeprazole reduced tyrosinase protein abundance in the presence of cycloheximide, suggestive of increased degradation. Our findings are consistent with the hypothesis that omeprazole reduces melanogenesis by inhibiting ATP7A and by enhancing degradation of tyrosinase.